Existence and Ulam stability for nonlinear implicit fractional differential equations with Hadamard derivative - BENCHOHRA, Mouffak; LAZREG, Jamal E. (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
The purpose of this paper is to establish some types of Ulam stability: Ulam-Hyers stability, generalized Ulam-Hyers stability, Ulam-Hyers-Rassias stability and generalized Ulam-Hyers-Rassias stability for a class of implicit Hadamard fractional-order differential equation. Mathematics Subject Classification (2010): 26A33, 34A08.